2017
DOI: 10.1111/tbj.12930
|View full text |Cite
|
Sign up to set email alerts
|

Invasive breast carcinomas withATMgene variants of uncertain significance share distinct histopathologic features

Abstract: The increasing availability of next-generation sequencing for clinical research dramatically improved our understanding of breast cancer genetics and resulted in detection of new mutation variants. Cancer risk data relating to some of these variants are insufficient, prompting the designation of variants of uncertain significance (VUS). The histopathologic characteristics of these variants have not been previously described. We propose to depict these characteristics and determine if invasive carcinomas with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Moreover, we did not observe an association between ATM variant status of the patient and clinical stage and histology criteria associated with aggressive tumors (for example, embolus, high mitotic index, triple-negative histological subtype), which is interesting in the discussion of the adjuvant RT treatment schedule of carriers of ATM PV or PPV who do not seem to have more aggressive histological characteristics than noncarrier patients. An exploration of a possible difference in histological subtypes of breast cancer in ATM variant carriers compared to other genes implicated in DNA double-strand break repair, such as BRCA1 and BRCA2, was conducted by Abdulrahman et al in 2018 and showed that tumors of ATM VUS carriers seem smaller, with lower pathologic T stages at diagnosis and greater surrogate molecular subtypes [37]. In a previous study, we performed a systematic pathology review of breast tumors from 21 ATM PV carriers from A-T families and 18 PV or predicted PV carriers from Hereditary Breast and Ovary Cancer families (including patients enrolled in CoF_AT2 and GENESIS), and we found that ATM-associated breast tumors belong mostly to the luminal B subtype in a retrospective tumor [38].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not observe an association between ATM variant status of the patient and clinical stage and histology criteria associated with aggressive tumors (for example, embolus, high mitotic index, triple-negative histological subtype), which is interesting in the discussion of the adjuvant RT treatment schedule of carriers of ATM PV or PPV who do not seem to have more aggressive histological characteristics than noncarrier patients. An exploration of a possible difference in histological subtypes of breast cancer in ATM variant carriers compared to other genes implicated in DNA double-strand break repair, such as BRCA1 and BRCA2, was conducted by Abdulrahman et al in 2018 and showed that tumors of ATM VUS carriers seem smaller, with lower pathologic T stages at diagnosis and greater surrogate molecular subtypes [37]. In a previous study, we performed a systematic pathology review of breast tumors from 21 ATM PV carriers from A-T families and 18 PV or predicted PV carriers from Hereditary Breast and Ovary Cancer families (including patients enrolled in CoF_AT2 and GENESIS), and we found that ATM-associated breast tumors belong mostly to the luminal B subtype in a retrospective tumor [38].…”
Section: Discussionmentioning
confidence: 99%
“…Variants of uncertain significance have also been identified in other genes such as: TP53 (15), ATM (16) or PALB2 (17). There are only few studies, which describe histopathologic characteristics of VUS (18).…”
Section: Introductionmentioning
confidence: 99%